Influence of graphene wrapped-cerium oxide coating on spherical LiNi0.5Mn1.5O4 particles as cathode in high-voltage lithium-ion batteries - Zawar Alam Qureshi (17545743) (2022)
Cobalt-free ﻿LiNi0.5Mn1.5O4 (Lithium Nickel Manganese Oxide; LNMO) has garnered considerable interest as a cathode material due to its high working voltage, lower cost, and environmental friendliness. However, LNMO cathodes currently exhibit low cyclability and capacity deterioration, severely restricting their use on a broader scale. To this end, microwave-assisted chemical co-precipitation was used to produce spherical aggregated nanoparticles of LiNi0.5Mn1.5O4 (LNMO) coated with CeO2 (LNMO-Ce) and wrapped in graphene (LNMO-Ce-GO). Structural analysis demonstrates that the ceria coating along with the graphene wrapping prevents unwanted phases from forming and altering the morphology of the LNMO microspheres. LNMO-Ce-GO exhibits a discharge capacity of 132.4 mAhg−1 at the C/10 rate with a capacity retention of 95.3 % after 100 cycles, compared to LNMO-Ce and bare LNMO samples that provide a capacity retention of 91.6 % and 84.7 % respectively. DSC analysis elucidate that the ceria coating helps to suppress the adverse reactions at the electrode/electrolyte interface and reduce the Mn3+ dissolution due to the Jahn Teller effect, increasing cell cyclability. The graphene wrapping reduces material aggregation and provides conductive pathways that significantly improve the electrochemical performance of the LNMO cathode. This innovative material design strategy can be efficiently expanded to other classes of lithium-ion battery cathode materials to enhance their electrochemical performance. Other Information Published in: Journal of Alloys and Compounds License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jallcom.2022.165989